Primary Burkitt lymphoma of the supraglottic larynx: a case report and review of the literature - Quimby, Alexandra E; Caulley, Lisa; Rodin, Danielle; Purgina, Bibianna; Eapen, Libni; Shier, Luke; Johnson-Obaseki, Stephanie (Université d'Ottawa | University of Ottawa, 2017)
Abstract Background Burkitt lymphoma is a high-grade B cell lymphoma which accounts for less than 1% of all adult cases of non-Hodgkin lymphoma. Rare instances of Burkitt lymphoma developing secondary to prior irradiation have been described in the literature. Case presentation We report a case of a 90-year-old white woman with a recent history of irradiation for Hodgkin lymphoma, who presented with primary Burkitt lymphoma of the supraglottic larynx. She underwent emergency awake tracheostomy with biopsy. A histopathological examination confirmed non-Hodgkin, B cell lymphoma of Burkitt type. Given her age and poor functional status, she underwent treatment with palliative radiotherapy. Conclusions A literature review was performed to clarify the clinical characteristics of radiation-induced Burkitt lymphoma in the head and neck, as well as its diagnosis and management. The present case represents the second case of radiation-induced Burkitt lymphoma in the head and neck in the reported literature, and the first in the supraglottic larynx. It highlights the need to maintain a broad differential in the assessment of malignancies of the larynx, particularly in patients with a prior history of radiation treatment.